Optical properties of LiNbO₃:Zn and LiNbO₃:Zn:Nd fiber single crystals grown by micro-pulling down method - H.J. Lee; J.W. Shur; O. Nakamura; D.H. Yoon (Functional Materials, 2007)
The present interest in small compact diode pumped lasers has supported research on new solid state laser systems based on non-linear crystals. High quality LiNbO₃ fiber single crystals were grown by micro-pulling down method. It was found indirectly from the optical properties of the LiNbO₃ fiber single crystals that doping those with ZnO increases their photorefractive resistance. In addition, photoluminescence properties due to the addition of Nd₂O₃ dopant have been investigated.